2010
DOI: 10.1260/0309-524x.34.5.531
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on the Assessment of Wind Energy Potential in Gaza Strip

Abstract: The analysis of collected wind data at two sites in Gaza Strip namely, Gaza city and Gaza International Air Port in Rafah city is presented. The two sites are candidates for remote area wind energy applications The purpose of this paper is to present the results of the assessment of wind energy potential in Gaza Strip in order to evaluate the wind regimes for installing wind energy conversion systems for power generation. The data on wind speed, direction and frequency distribution are used to analyze wind ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Electricity is not always available to many Palestinians, especially in Gaza Strip. According to a research performed by Oxfam in April 2010, it showed that houses across Gaza Strip were without power for about 35-60 hours per week [27,28]. According to PCBS 2013 data, 99.8 % households in West Bank have a 24-hour access to power, and the daily power service for 97.2 % of households in Gaza Strip is barely 16 hours [12].…”
Section: Energy Status In Palestinementioning
confidence: 99%
See 3 more Smart Citations
“…Electricity is not always available to many Palestinians, especially in Gaza Strip. According to a research performed by Oxfam in April 2010, it showed that houses across Gaza Strip were without power for about 35-60 hours per week [27,28]. According to PCBS 2013 data, 99.8 % households in West Bank have a 24-hour access to power, and the daily power service for 97.2 % of households in Gaza Strip is barely 16 hours [12].…”
Section: Energy Status In Palestinementioning
confidence: 99%
“…This result corresponds to the results Elnaggar was found. Alaydi concluded that the annual highest attainable wind power potential per unit area of the wind stream is about 0.5 MWhr/m 2 /year [27,28,39]. [29].…”
Section: Monthsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alaydi presented a parametric study of solar and wind energy in the Gaza Strip in which wind power was compared with solar irradiance. Results showed that a large stand‐alone PV or wind energy converter will be needed to supply the peak demand in the months from June to September 26 …”
Section: Introductionmentioning
confidence: 99%